DOI: 10.14264/uql.2017.987
|View full text |Cite
|
Sign up to set email alerts
|

Adults with mild hearing impairment: Measuring real-world hearing performance

Abstract: The World Health Organization recognizes acquired hearing impairment as the third leading cause of disability worldwide, with a mild hearing impairment the most prevalent.Between 1 in 3 and 1 in 5 adults have a mild hearing impairment, with prevalence rising with age. Studies of other age-related changes, for example in cognition and physical activities, suggest that declines in these functions may be exacerbated if hearing impairment is not addressed at an early stage.Few studies, however, have focused specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The findings from this previous EMA study demonstrated that in 91% of the 962 speech-listening surveys collected, speech understanding was rated as either ''75%'' or ''100%,'' and in only 9% of listening events, speech understanding was rated as ''0%,'' ''25%,'' or ''50%'' (Timmer, 2017). However, although the participants self-reported very good or excellent speech understanding in their common listening events, they also rated the events as needing relatively more effort to reach that level.…”
Section: Introductionmentioning
confidence: 82%
“…The findings from this previous EMA study demonstrated that in 91% of the 962 speech-listening surveys collected, speech understanding was rated as either ''75%'' or ''100%,'' and in only 9% of listening events, speech understanding was rated as ''0%,'' ''25%,'' or ''50%'' (Timmer, 2017). However, although the participants self-reported very good or excellent speech understanding in their common listening events, they also rated the events as needing relatively more effort to reach that level.…”
Section: Introductionmentioning
confidence: 82%